2291. A Real-Time Sequencing Approach for Simultaneous Metagenomic and Transcriptomic-Based Diagnosis of Infectious Diseases. (26th November 2018) - Briggs, Benjamin; Federman, Scot; Deng, Xian Ding; Gu, Wei; Yu, Guixia; Martin, Claudia Sanchez San; Miller, Steve; Chiu, Charles Y
Abstract: Background: Recent studies have demonstrated the utility of metagenomic next-generation sequencing (mNGS) and RNA gene expression sequencing (RNA-Seq) for identifying causes of infections. Although these approaches have been largely tested to date using established sequencing platforms such as the Illumina HiSeq, the use of nanopore sequencing on the MinION sequencer (Oxford Nanopore Technologies) is attractive given rapid library preparation and real-time analysis of sequencing data resulting in accelerated sample-to-answer turnaround times. Methods: We have developed a rapid molecular concatemerization library approach to increase the throughput of the nanopore sequencer analysis for metagenomic and RNA-Seq approaches. We have also developed a pipeline (SURPI rt, "Sequence-based ultra-rapid pathogen identification, real-time") that allows for real-time, simultaneous metagenomic and transcriptomic analyses on the same sample. Results: With the use of molecular concatemerization library approach, we show that metagenomic and transcriptomic data generated on the MinION are comparable to those on the Illumina platform, yet can be collected and analyzed in significantly less time (6 hours vs. 2–3 days). Conclusion: Here we demonstrate simultaneous metagenomic and RNA-Seq analyses on a nanopore-based sequencing platform with real-time analysis of results. We foresee that this approach could be leveraged into a rapid screening test for diagnosis of infectious diseases in both hospital and field settings. Disclosures: All authors: No reported disclosures.